Women Who Live Evil Lives Gender, Religion, and the Politics of Power in Colonial Guatemala - Few, Martha 1964- (University of Texas Press, 2021)
Women Who Live Evil Lives documents the lives and practices of mixed-race, Black, Spanish, and Maya women sorcerers, spell-casters, magical healers, and midwives in the social relations of power in Santiago de Guatemala, the capital of colonial Central America. Men and women from all sectors of society consulted them to intervene in sexual and familial relations and disputes between neighbors and rival shop owners; to counter abusive colonial officials, employers, or husbands; and in cases of inexplicable illness. Applying historical, anthropological, and gender studies analysis, Martha Few argues that women's local practices of magic, curing, and religion revealed opportunities for women's cultural authority and power in colonial Guatemala. Few draws on archival research conducted in Guatemala, Mexico, and Spain to shed new light on women's critical public roles in Santiago, the cultural and social connections between the capital city and the countryside, and the gender dynamics of power in the ethnic and cultural contestation of Spanish colonial rule in daily life